2022
DOI: 10.1021/acs.langmuir.2c00853
|View full text |Cite
|
Sign up to set email alerts
|

Ag and Au Nanoparticles as Color Indicators for Monomer/Micelle–Nanoparticle Interactions

Abstract: Ag and Au nanoparticles (NPs) were used as color indicators to determine the monomer/micelle adsorption on the NP surface. A simple methodology based on the color change of Ag/Au NPs upon interacting with surface-active molecules was developed. A contrasting color change occurred when NPs interact with the monomer/micelle. This was demonstrated by monitoring the adsorption behavior of a series of Gemini surfactants. UV–visible measurements showed a large change in the intensity and wavelength of Ag/Au NP absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…6 Surfactants capped zerovalent iron NPs were used as an adsorbent to the extraction of protein stabilized gold NPs from an aqueous bulk. 7,8 Surfactants (cationic, anionic and nonionic) were also employed as a solubilizing media for oily sludge 9 and coal tar 10 to the degradation of aromatic hydrocarbons by thermally activated persulfate. Xue et al 9 and Deng et al 10 suggested that the surfactant could solubilized the oily sludge and coal tar components such as saturated and polyaromatic hydrocarbons into the deep hydrophobic core, and increases the solubility by reducing the surface tension in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…6 Surfactants capped zerovalent iron NPs were used as an adsorbent to the extraction of protein stabilized gold NPs from an aqueous bulk. 7,8 Surfactants (cationic, anionic and nonionic) were also employed as a solubilizing media for oily sludge 9 and coal tar 10 to the degradation of aromatic hydrocarbons by thermally activated persulfate. Xue et al 9 and Deng et al 10 suggested that the surfactant could solubilized the oily sludge and coal tar components such as saturated and polyaromatic hydrocarbons into the deep hydrophobic core, and increases the solubility by reducing the surface tension in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…13 Metal NPs, such as Ag, Au, and Fe, have been used for dye adsorption due to their unique surface properties. 14 oxide NPs, such as TiO 2 , 15 SnO 2 , 16 and ZnO, 15 have also been studied for dye adsorption due to their photocatalytic activity. However, the usage of green nanoadsorbents promotes the adoption of sustainable methods that will boost the green economy.…”
Section: Introductionmentioning
confidence: 99%
“…Metal NPs, such as Ag, Au, and Fe, have been used for dye adsorption due to their unique surface properties . Metal oxide NPs, such as TiO 2 , SnO 2 , and ZnO, have also been studied for dye adsorption due to their photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The nanoparticles have been investigated for the removal of environmental contaminants because they are inert, economical, possess high surface area, and have the ability for its surface modifications. 23,24 Additionally, the small dosage of nanoparticles have high efficiency in the treatment of large quantity of contaminants. However, the nanoparticles have its own some shortcomings like agglomeration into larger particle size, potential exposure and entry into the human body and limited working pH range.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, iron (II) oxide nanoparticles‐H 2 O 2 has been investigated for its catalytic activity in placed the Fe 2+ ‐H 2 O 2 system for the environmental remediation of various contaminants 21,22 . The nanoparticles have been investigated for the removal of environmental contaminants because they are inert, economical, possess high surface area, and have the ability for its surface modifications 23,24 . Additionally, the small dosage of nanoparticles have high efficiency in the treatment of large quantity of contaminants.…”
Section: Introductionmentioning
confidence: 99%